Analysis of antiviral efficacy after switching from brand to generic entecavir in patients with treatment-naïve chronic hepatitis B - Po-Ke Hsu (BMC Gastroenterology, 2022)
Abstract Background/Aims Entecavir (ETV) can suppress chronic hepatitis B (CHB) virus replication as a standard of treatment drugs. For the treatment of CHB, affordable generic drugs may be more widely used in developing and undeveloped countries. However, there is little real-world data regarding the clinical efficacy of switching from entecavir-brand-name drugs (ETV-Brand) to entecavir generic drugs (ETV-Generic) with 0.5 mg once daily. The aim of the study was to evaluate the antiviral activity and safety of ETV-Generic in comparison to ETV-Brand in CHB-patients. Methods In this single-center, retrospective, 175 treatment-naïve—CHB-patients were assigned to receive 0.5 mg of ETV-Brand per day for a least 2 years and then switched to ETV-Generic for 6 months for analysis. The primary efficacy endpoint was a sustained virological response in comparison of the rate of undetectable serum Hepatitis B deoxyribonucleic acid (HBV DNA) as the sustained virologic response at baseline and 6 months after switching. Secondary efficacy endpoints were the comparison of the alanine aminotransferase (ALT) levels between before and after switching and ALT normalization. Renal safety consideration was reported on changing the estimated glomerular filtration rate. Results From baseline to 6 months, the rate of undetectable HBV DNA and ALT levels remained stable as compared ETV-Brand period with ETV-Generic for 6 months. The rate of undetectable HBV DNA were 81.1%in ETV-Brand versus 88.0%in ETV-Generic (p = 0.05 CI 0.1–13.5%). ALT levels were 27.2 IU/L (CI 24.8–29.6 IU/L) in ETV-Brand versus 26.2 IU/L (CI 24.0–28.4 IU/L) in ETV-Generic (p = 0.55). Both endpoints were not significantly different between ETV-Brand and ETV-Generic treatments. Kidney function did not significantly differ from ETV-Brand (80.8, interquartile range [IQR]: 66.6–95.3 mL/min/1.73 m2) to ETV-Generic treatment period (80.3, IQR: 65.6–93.5 mL/min/1.73 m2). Conclusion In treatment-naïve CHB-patients, the efficacy and safety profiles of switching from ETV-Brand to ETV-Generic showed no difference. Concluding the ETV-Generic comes to exciting virologic responses and rare adverse events.